Mob or Army: Metaphors for Knowledge Organization - Olson, Hope A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Much of western philosophy implies a notion of hierarchy. Systems for topical organization of information typically exhibit hierarchical structures. This paper will examine two schools of philosophy and two streams of organization of information to trace the influence of philosophy on the founders of our systems and their current manifestations with an emphasis on their hierarchical leanings.